Multi-dimensional price elasticity for leisure and business destinations in the low-cost air transport market: Evidence from easyJet. (August 2017) - Morlotti, Chiara; Cattaneo, Mattia; Malighetti, Paolo; Redondi, Renato
Abstract: This study investigates the price elasticity of demand in the European low-cost carrier (LCC) industry by analysing Internet fares for all easyJet flights departing from the Amsterdam Schiphol airport towards 21 European destinations between March and September 2015. Results suggest that the price elasticity of demand greatly varies across different dimensions, ranging from −0.535 for the business-oriented route of Hamburg to −1.915 for the leisure-oriented route of Split. Price elasticity is also found to be higher for reservations made more days in advance, for reservations and departures occurring on weekends, and for flights taking off during lunchtime and in the summer period. All results are consistent with the different behaviours of leisure and business passengers and the ongoing increase in the business component of the LCC passenger mix. Highlights: This article analyses price elasticity of demand for leisure and business destinations. easyJet's price elasticity of flights departing from the AMS airport is overall inelastic. During the summer, price elasticity of demand on average increases. Price elasticity is higher for weekends-reservations and -departures and lunchtime flights. Price elasticity is higher for reservations made more days in advance.